Strong carrier lifetime enhancement in GaAs nanowires coated with semiconducting polymer. - Yong, C; Noori, K; Gao, Q; Joyce, H; Tan, H; Jagadish, C; Giustino, F; Johnston, M; Herz, L (2012)
The ultrafast charge carrier dynamics in GaAs/conjugated polymer type II heterojunctions are investigated using time-resolved photoluminescence spectroscopy at 10 K. By probing the photoluminescence at the band edge of GaAs, we observe strong carrier lifetime enhancement for nanowires blended with semiconducting polymers. The enhancement is found to depend crucially on the ionization potential of the polymers with respect to the Fermi energy level at the surface of the GaAs nanowires. We attribute these effects to electron doping by the polymer which reduces the unsaturated surface-state density in GaAs. We find that when the surface of nanowires is terminated by native oxide, the electron injection across the interface is greatly reduced and such surface doping is absent. Our results suggest that surface engineering via π-conjugated polymers can substantially improve the carrier lifetime in nanowire hybrid heterojunctions with applications in photovoltaics and nanoscale photodetectors.